Water quality from Koçkale and Pertek regions of Keban dam Lake (Elazi?/TURKEY) on ovarium tissue of capoeta trutta (Heckel,1843) histopathological effect - Ural, Mesut; Özdemir, Yaşar (My University, 2011)
In this study the changes of physical and chemical characteristics of water obtained from pointed stations of Koçkale and Pertek regions of Keban Dam Lake and for this purpose, water temperature, dissolved oxygen, pH, nitrate, nitrite, ammonia, free CO2, phosphate, calcium hardness, magnesium hardness, free chloride and total hardness have been monthly analysed. At the same time, a total number of 367 Capoeta trutta (Heckel, 1843) have been caught and macroscopic and microscopic features of ovarium of 182 female from Koçkale region and 185 female from Pertek region have been examined. Macroscopically; it was observed that the ovariums of fish from Pertek region showed better development than those from Koçkale region. Microscopically; it was also observed that the atretic folicula (development uncompleted, but oocyte stage unable to reach ovulation because of environmental factors) numbers in the ovariums of fish from Koçkale region showed an obvious increase compared with that from Pertek region. It was concluded that ovarium development of the fish was negatively affected as a result of the changes in chemical parameters of ammonia, nitrate and phosphate in Lake water with discharging of sewage from Elazi{dotless}? city into Keban Dam lake at Koçkale region.
Keywords: Capoeta trutta; Keban dam lake; Ovarium tissue; Water quality